1998
DOI: 10.1111/j.1467-842x.1998.tb01180.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of different alcoholic beverages as predictors of local rates of night-time assault and acute alcohol-related morbidity

Abstract: here has been considerable academic and media interest in recent times in T the allegedly beneficial effects of specific varieties of alcoholic drinks. A study published in The Lancet in 1995' purported to demonstrate that wine drinkers lived longer than beer or spirit drinkers, even when potentially confounding sociodemographic factors were allowed for. Laboratory studies have indicated that red rather than white wine contains ingredients (clearly not alcohol) which are effective in reducing blood lipoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 8 publications
2
39
0
1
Order By: Relevance
“…This comparison shows that while the two estimates are broadly comparable, regular strength beer, cask wine and fortified wine were underestimated by the survey method, probably reflecting the difficulty of sampling high risk drinkers in household surveys. Previous research has demonstrated that high local per capita consumption of these beverages is most likely to be associated with high local rates of serious alcohol-related harm (Stockwell et al, 1998;Gray et al, 2000). The comparison also suggests that spirit consumption tends to be slightly underestimated by the survey method employed.…”
Section: Per Capita Alcohol Consumption In Australia Of Persons Aged mentioning
confidence: 53%
See 2 more Smart Citations
“…This comparison shows that while the two estimates are broadly comparable, regular strength beer, cask wine and fortified wine were underestimated by the survey method, probably reflecting the difficulty of sampling high risk drinkers in household surveys. Previous research has demonstrated that high local per capita consumption of these beverages is most likely to be associated with high local rates of serious alcohol-related harm (Stockwell et al, 1998;Gray et al, 2000). The comparison also suggests that spirit consumption tends to be slightly underestimated by the survey method employed.…”
Section: Per Capita Alcohol Consumption In Australia Of Persons Aged mentioning
confidence: 53%
“…Gray, 2000) as well as for numerous local, regional and jurisdiction-wide monitoring exercises (e.g. Stockwell et al, 1998;. In the present study, accurate trends in population levels of alcohol consumption after the financial year 1995/1996 were only possible for Western Australia and the Northern Territory (Queensland has only recently re-started data collection).…”
Section: Data Sourcesmentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, the least taxed beverages in the U.S. (Rogers and Greenfield, 1999) and Australia (Stockwell et al, 2008), beer and cask wine respectively, are exactly those considered most associated with alcohol-related harms in each country. Moreover, in the LAC region, alcohol-advertising restrictions are commonly distinguished by beverage types but are not grounded on the scientific evidence available on the harmful effects of each type of alcoholic beverage (Pechansky et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Literature reviews have repeatedly identified raising the price of alcohol as one of the most consistently effective policy interventions available to government [9,10]. A further increase in the price of cask wine was introduced in July 1995 as a consequence of concern about excessive drinking associated with this cheapest of alcoholic beverages [11].…”
Section: Price Increasesmentioning
confidence: 99%